Improvement of Renal Function by Long-Term Sustained Eculizumab Treatment in a Patient with Paroxysmal Nocturnal Hemoglobinuria - Haruhiko Ninomiya; Naoshi Obara; Akiko Niiori-Onishi; Yasuhisa Yokoyama; Mamiko Sakata-Yanagimoto; Yuichi Hasegawa; Shigeru Chiba (Case Reports in Hematology)
Chronic kidney disease (CKD) is one of the major manifestations of paroxysmal nocturnal hemoglobinuria (PNH). CKD in PNH is induced mainly by intravascular hemolysis of PNH-affected red blood cells (RBC) missing the glycosylphosphatidylinositol-anchored proteins with complement-regulatory activities, CD55 and CD59. CKD develops by heme absorption in the proximal tubules resulting in the interstitial deposition of iron in the kidneys. We administered eculizumab to a patient with PNH, who was one of 29 patients enrolled in the AEGIS clinical trial, an open-label study of eculizumab in Japan. The patient was complicated by stage 3 CKD with impaired estimated glomerular filtration rate (eGFR), at grade G3b, and had obvious proteinuria (2-3+, 1-2 g/day). In a two-year extension to the 12-week AEGIS study, eGFR improved significantly, and the eGFR has since been maintained at grade G2 without proteinuria by sustained eculizumab treatment (>6 years). Renal function improved and maintained by long-term sustained eculizumab treatment, presumably by clearance of iron from the kidney as well as inhibition of the production of anaphylatoxin C5a, even in advanced stages of CKD, is one of the benefits of eculizumab treatment in PNH.